Edge detection for detection of brain tumour in CT images - R. Thamizhvani, T; Josephin Arockia Dhivya, A; Akshaya, S; Dhanalakshmi, K; Chandrasekaran, R; Elsa Joseph, Josline (International Journal of Engineering and Technology, 2018)
Brain tumour can be defined as the continuous and uncontrolled growth of the cells in the regions of brain. Analysis and detection of brain tumours from the computed tomography images can be performed by various image processing algorithms. Edge detection is special type of image processing technique, which uses operators for functioning. The Computed Tomography images are obtained from the standard data-base which undergoes pre-processing technique. Contrast adjustment is performed to enhance the region of brain tumour. Edge operators of different types are applied to the images for identification of the boundary of the brain tumour region. Appropriate edge operator for de-termination of the boundary is defined by comparing the image quality and accuracy parameters. These parameters illustrate that canny oper-ator is described to be more definite for the detection and analysis of the boundary and region of brain tumour in Computed Tomography images.Â Â Â